Dufour effect on unsteady natural convection flow past an infinite vertical plate with constant heat and mass fluxes - Tippa, S. (American Institute of Physics Inc., 2014)
In this paper, Dufour effect on unsteady natural convection flow near an infinite vertical plate with constant heat and mass fluxes has been investigated analytically. The resulting system of coupled linear partial differential equations is solved using the Laplace transform technique. Closed form analytical solutions are obtained for the velocity, temperature and concentration fields, skin-friction, Nusselt and Sherwood numbers. The effect of Dufour number on the velocity and temperature fields, skin-friction and Nusselt number have been discussed through graphs and tables. The study revealed that the Dufour number has significant influence on the velocity and temperature fields. Â© 2014 AIP Publishing LLC.